PENGARUH LARUTAN PERENDAM SARI BELIMBING WULUH DAN GULA TERHADAP VASE LIFE BUNGA POTONG KRISAN STANDAR PUTIH (Dendranthema grandiflora L.) ‘WHITE FIJI’ - Anang Dwi Laksono; Nugraheni Widyawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
ABSTRACT  Chrysanthemum cut flowers  (Dendranthema grandiflora L.) after harvest have a short vase life, so that efforts are needed to extend the freshness period. The basic principle of extending the freshness of cut flowers is through soaking in water containing sugar, controlling acidity, and microbes in the soaking solution. This research aims to determine the effect of wuluh starfruit extract and sugar concentrations in the soaking solution on the vase life of chrysanthemums. The research was conducted using Randomized Block Design (RBD) consisting two factors, that is concentration of wuluh starfruit (Averrhoa bilimbi Linn.) with variations concentration  0% (B0), 1% (B1), 2% (B2), 3% (B3) and white crystalline sugar with variations concentration 0% (S0), 1% (S1), 2% (S2), 4% (S3), so there are 16 treatment combinations. Each treatment was three repetitions. Data were analyzed using Analysis of Variants (ANOVA) followed by an Honestly Significant Difference Test (BNJ) with a 95% confidence levels. The results showed that treatment giving of wuluh starfruit extract 2% + 1% of sugar (B2S1) was able to maintain chrysanthemum cut flowers during storage with maintaining flower vase life up to 17.80 days. Keywords: Chrysanthemum, soaking solution, vase life